1994
DOI: 10.1111/j.1532-5415.1994.tb01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Visual Impairment with Mobility and Physical Function

Abstract: Distant visual function appears to play an important role in physical function, particularly for mobility. An intervention to improve vision in at-risk elders might preserve function and prevent disability; this warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
159
1
12

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(180 citation statements)
references
References 27 publications
8
159
1
12
Order By: Relevance
“…Despite these changes, the importance of vision to maintain postural control seems to increase with age (Woollacott 2000). Vision also plays an important role in mobility performance (Salive et al 1994). Therefore it is not surprising that impaired vision has been reported as a major risk factor for falls among older adults (Lord 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these changes, the importance of vision to maintain postural control seems to increase with age (Woollacott 2000). Vision also plays an important role in mobility performance (Salive et al 1994). Therefore it is not surprising that impaired vision has been reported as a major risk factor for falls among older adults (Lord 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found a strong relationship between visual impairment and functional disability among community-based older adults, even after controlling for demographic and comorbid health conditions [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. When compared with other physical impairments, visual impairment also has a more severe effect on everyday functioning and is as limiting as terminal cardiac disease in older adults [23].…”
Section: Visual Impairmentmentioning
confidence: 99%
“…A obsessão pela aparência desvaloriza aqueles que não preenchem o ideal concebido e estigmatiza aqueles com deformidades visíveis (12) . A diminuição da capacidade visual em geral também tem grande impacto na capacidade funcional diária e no bem-estar dos pacientes (13)(14) . Nas últimas décadas, o interesse crescente da comunidade científi-ca e de todo o setor de saúde em questões de qualidade de vida levou a um desenvolvimento marcante desse conceito (15) .…”
unclassified